A Stock Assessment of the Blue Swimming Crab Portunus pelagicus (Linnaeus, 1758) for Sustainable Management in Kung Krabaen Bay, Gulf of Thailand - Chutapa Kunsook; Nantana Gajaseni; Nittharatana Paphavasit (Tropical Life Sciences Research, 2014)
A stock assessment of blue swimming crabs, Portunus pelagicus was conducted with crab gill nets and collapsible crab traps at Kung Krabaen Bay, in the eastern Gulf of Thailand, from 2008 to 2009. Several key indicators show that P. pelagicus population is in crisis. Fishing mortality shows an increase to 4.14. The exploitation rate is 0.71, higher than the optimal value of 0.38. The size of the mature females has also decreased from 8.10±0.39 cm to 7.52±1.14 cm. The average fecundity is 0.572x106 ±0.261x106 eggs per batch, and the sex ratio (male:female) is 1:0.92. Based on these results, a sustainable management program for P. pelagicus was proposed as follows: (i) closing the bay during the spawning season, (ii) restoration of the Enhalus acoroides seagrass beds, (iii) restocking crab larvae in the bay and (iv) educating and networking all stakeholders to develop a better understanding of the ecology of the crab to support sustainable fishery management in Kung Krabaen Bay. Satu penilaian stok ketam renjong, Portunus pelagicus telah dijalankan menggunakan crab gill net dan collapsible crab trap di Kung Krabaen Bay, yang terletak di timur Teluk Thailand, dari 2008 hingga 2009. Beberapa indikator penting telah menunjukkan bahawa populasi P. pelagicus menghadapi krisis. Mortaliti tangkapan menunjukkan peningkatan kepada 4.14. Kadar eksploitasi ialah 0.71, iaitu lebih tinggi daripada nilai optimum 0.38. Saiz ketam betina matang juga telah berkurangan dari 8.10±0.39 cm kepada 7.52±1.14 cm. Nilai purata fekunditi ialah 0.572x106 ±0.261x106 telur setiap kelompok, dan nisbah jantina (jantan:betina) ialah 1:0.92. Berdasarkan keputusan ini, suatu program pengurusan lestari untuk P. pelagicus telah dicadangkan seperti berikut: (i) menutup teluk semasa musim mengawan, (ii) pemulihan semula tapak rumput laut Enhalus acoroides, (iii) penstokan semula larva ketam di teluk dan (iv) mendidik dan mewujudkan rangkaian sosial antara kesemua pemegang taruh untuk membina pemahaman yang lebih baik terhadap ekologi ketam dalam menyokong pengurusan perikanan secara lestari di Kung Krabaen Bay.